A novel discovery platform for targeted drug repurposing: application for psychiatric disorders - Berk, Michael; Kim, Jee Hyun; Williams, Lana J; Liu, Zoe S J; Siskind, Dan; Panizzutti, Bruna; Yung, Alison R; Walder, Ken (The Lancet. Psychiatry, 2025)
Existing pharmacotherapies and psychotherapies are often inadequate, and discovery for new pharmacological treatments in psychiatry is slow. Existing pharmacotherapies are, however, often inadequate. Few truly novel pharmacotherapies have emerged in the past four decades, largely due to the absence of a known pathophysiology for each disorder. In this Personal View, we describe the platform we have adopted that enables targeted drug repurposing. With this approach, patient-derived stem cells are used to detect transcriptomic targets to identify existing drugs that address these targets. These drugs are then validated in non-human animal models and pharmacoepidemiological studies before being tested in clinical trials. Our targeted drug repurposing platform bypasses the absence of known pathophysiology. Validation steps bring greater scientific rigour and mechanistic insights to drug repurposing to allow only drug candidates with the strongest mechanistic evidence to be tested in clinical trials.